FORM AND FUNCTION OF MAIN NEWS SPEECH ACTS IN WASPADA NEWSPAPER - Muhammad Kiki Wardana (Rahis Cendekia Indonesia, 2023)
This descriptive study aims to find out (1) the type of speech acts in the main news story of Wasapada newspaper, (2) the form of speech acts in the main news story of Waspada Post newspaper, and (3) the function of speech acts in the main news story of Waspada Post newspaper. The research object is sentences about the main news of Wasapada newspaper. Data was collected through a documentation method using data tag tools. Based on the analysis carried out, the results of this study show that (1) the main news stories in Wasapada newspaper all contain speech and expression acts, (2) the dominant form used in the main news is the reporting form 27, (3) the main form of news contains speech act function, affirmative function is 27, directive function is 4, expressive function is 1, declarative function is 1 and it n has no function delegate. Among these functions, there is a more prominent function used in important news, which is the decisive function. Assertive function was divided into three such as, explaining assertive, announcing assertive, and presuming assertive. Assertive function dominantly used because that function was useful as an expression to explaining speech, presuming speech and announcing speech to the opponent of speech.